COMPARATIVE STUDY ON BACTERIAL PLAQUE AND GINGIVITIS HEALTH STATUS INDICATORS - Carina Balcoș; Ioan Dănilă; Iulia Săveanu (Romanian Dental Association for Education, 2014)
Introduction: The population is becoming more aware of the importance of oral hygiene in maintaining the health of the entire body. It is well known that the plaque is the main etiological factor in producing caries disease and periodontal disease. The purpose of this study was to evaluate the comparative value of indices of plaque and gingival inflammation in a group of yougers. Materials and methods: The study was conducted on a sample of 122 subjects. The study was clinical type. Data were collected after completion of revelation and clinical examination plaque noting the index values calculated for each observation sheet. The clinical evaluation of oral hygiene status, we used the API index (Approximal Plaque Index) and BI (bleeding index) indices for assessing periodontal status. All subjects included in the study were informed verbally about the purpose of the study noting the consent form. Examination of patients was performed in the Office Polyclinic No. 1, Ambulatory of Dentistry. Patients were placed in the database according to certain codes. Statistical data processing was done with software for Windows SPSS 14.00 settling a threshold of statistical significance of p ≤ 0.05. Results and Discussion: Comparative analysis of plaque presence and degree of gingival inflammation revealed that the differences statistically significant p ≤ 0.05 for having an API index value averaged 72.71 (± 23.48) gingival index BI compared with a mean of 20.05 (± 18.32) and using dental wire influences the index of periodontal inflammation. Conclusions: Gingival inflammation is present in those with plaque and is subject to use wire but not the frequency of tooth brushing showing that adjuvant use of adjuvants to remove dental plaque but not entirely.